2014
DOI: 10.1007/s11249-014-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Stick–Slip Friction of Stainless Steel in Sodium Dodecyl Sulfate Aqueous Solution in the Boundary Lubrication Regime

Abstract: The objective of this study is to correlate the mass and structure of the adsorbed sodium dodecyl sulfate (SDS) on stainless steel surface in aqueous solution with the boundary lubrication behavior, especially the stick-slip phenomenon of the ZrO 2 /stainless steel friction pair. Surface tension measurement, quartz crystal microbalance (QCM) technique and ball-on-flat friction test were performed in this study. The adsorption isotherm of SDS on stainless steel surface in SDS aqueous solution was measured by QC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 52 publications
(96 reference statements)
7
21
1
Order By: Relevance
“…In addition to friction and lubrication experiments, to elucidate the mechanism of boundary lubrication, a thorough inspection of the boundary film is necessary [24]. Adsorption isotherms have long been used to study the adsorption properties of SAMs on a solid/liquid interface [30], but it was far from satisfactory to investigate the adsorption at an interface at the molecular level.…”
Section: Self-assembled Monolayers and Their Application In Boundary mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to friction and lubrication experiments, to elucidate the mechanism of boundary lubrication, a thorough inspection of the boundary film is necessary [24]. Adsorption isotherms have long been used to study the adsorption properties of SAMs on a solid/liquid interface [30], but it was far from satisfactory to investigate the adsorption at an interface at the molecular level.…”
Section: Self-assembled Monolayers and Their Application In Boundary mentioning
confidence: 99%
“…Using ZrO 2 ball and stainless steel plate as friction pair, Zhang and Meng [24] conducted a systematic study on the boundary lubrication performance, especially the stick-slip phenomenon in SDS aqueous solutions (2014). The SAMs formed on the steel surface by SDS molecules acts as boundary layer to provide lubrication during the sliding contact.…”
Section: The Relationship Between Adhesion and Stick-slip Phenomenonmentioning
confidence: 99%
“…Based on the friction and adsorption results, we suggest the friction modification mechanism of the gemini amphiphile. The key parameter determining the friction property is the adsorption mass of the amphiphiles at the silica/ester oil interfaces, as suggested previously in the aqueous surfactant systems 7,8,10 . The larger adsorption mass of the gemini amphiphile results in the formation of a rigid interfacial film, yielding greater stiffness against the normal load.…”
Section: Discussionmentioning
confidence: 89%
“…They presented a four-stage adsorption model at the solid/liquid interface. Later, Zhang et al [37] investigated the frictional behaviors of stainless steel in SDS aqueous solution, and found that the boundary lubrication behaviors are not only related to the mass and structure of the adsorbed SDS boundary film, but also affected by the driving speed and load.…”
Section: Introductionmentioning
confidence: 99%